1993
DOI: 10.1007/bf01605135
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of cardiac thrombosis in patients with atrial fibrillation in the absence of macroscopically visible thrombi

Abstract: Cardiac thrombosis due to atrial fibrillation (AF) has been recognized as the most common cause of cerebral embolism. However, sometimes no macroscopic thrombus is found at autopsy in the heart of a victim of this type of cerebral embolism. We investigated morphological changes in the left atrial endocardium of 31 patients (including 21 cases with AF) who had died of cerebral embolism. "Rough endocardium" (RE) seen macroscopically provided evidence for the existence of atrial thrombosis. The RE that appeared i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 12 publications
0
20
0
1
Order By: Relevance
“…It is interesting that Masawa et al reported morphological changes in the left atrial endothelium of AF patients who died from cerebral embolism; they had mural thrombi and edema with neutrophil infiltration in the subendocardium of the left atrial endocardium. 27 These results indicate a possibility that hemodynamic changes with AF were responsible for abnormalities in the functioning of left atrial endothelial cells.…”
Section: Cause Of Thrombus With Afmentioning
confidence: 81%
“…It is interesting that Masawa et al reported morphological changes in the left atrial endothelium of AF patients who died from cerebral embolism; they had mural thrombi and edema with neutrophil infiltration in the subendocardium of the left atrial endocardium. 27 These results indicate a possibility that hemodynamic changes with AF were responsible for abnormalities in the functioning of left atrial endothelial cells.…”
Section: Cause Of Thrombus With Afmentioning
confidence: 81%
“…Goldsmith and colleagues [7] have reported more severe endocardial changes in the LAA than in the right-atrial appendages, especially in atrial fibrillation (compared with sinus rhythm) and in mitral stenosis (compared with mitral regurgitation). Similarly, Masawa and co-workers [8] have described a "rough endocardium" with a wrinkled appearance attributable to oedema and fibrinous transformation; small areas of endothelial denudation and thrombotic aggregation have also been noted in patients with atrial fibrillation and cerebral embolism.…”
Section: Anatomical and Structural Considerationsmentioning
confidence: 85%
“…Masawa et al [159]. Described areas of endothelial denudation and thrombotic aggregation in the LA on scanning electron microscopy in subjects (n=31) who died from cerebral embolism, and these areas were more frequent when history of AF was documented (p<0.001) [159].…”
Section: 'Abnormal Vessel Wall'mentioning
confidence: 98%